2019
DOI: 10.1186/s12889-019-7643-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the built environment of Nanjing’s Urban Community on the leisure physical activity of the elderly: an empirical study

Abstract: BackgroundUrbanization and aging are global phenomena that offer unique challenges in different countries. A supportive environment plays an important role in addressing the issues of health behavioral change and health promotion (e.g., prevent chronic illnesses, promote mental health) among older adults. With the development of the socio-ecological theoretical model, studies on the impact of supportive environments on physical activity have become popular in the public health field in the EU and US. Meanwhile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 43 publications
5
45
0
2
Order By: Relevance
“…In our analysis of the relationship between BE and PA, BE attributes were related to total PA, transportation PA, and leisure time PA. This was consistent with the socio-ecological model [ 25 ] and several previous studies [ 26 , 27 , 28 , 29 , 30 , 31 ]. For example, aesthetics was positively associated with total and leisure-time PA in men, indicating aesthetics can motivate residents to engage in more PA [ 32 ] and men were more likely to conduct leisure-time activities in aesthetically pleasing spaces [ 33 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our analysis of the relationship between BE and PA, BE attributes were related to total PA, transportation PA, and leisure time PA. This was consistent with the socio-ecological model [ 25 ] and several previous studies [ 26 , 27 , 28 , 29 , 30 , 31 ]. For example, aesthetics was positively associated with total and leisure-time PA in men, indicating aesthetics can motivate residents to engage in more PA [ 32 ] and men were more likely to conduct leisure-time activities in aesthetically pleasing spaces [ 33 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…In our studies, crime safety was negatively correlated with reaction time. This is similar to previous studies’ results that lower criminal activity will increase the chance of residents going out to exercise [ 25 , 53 ] so indirectly improving the reaction time. Our research also analyzed the relationship between BE and the curl-up test, and the results indicated that aesthetics was positively associated with the curl-up test in men, and street connectivity was positively associated with curl-up test in women.…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, respondents who perceived that there was a low street connectivity tended to have a PA of C1. While [24,56] suggested that perceived street connectivity was usually positively associated with a high PA in older adults, as pointed out in [25], low street connectivity hinders PA levels because the areas usually have longer rows of housing, less traffic intersections and a higher number of dead-end roads less conducive for walking; therefore, the results of this study add to existing knowledge.…”
Section: Model 1 (Perling Terrace)supporting
confidence: 50%
“…Other studies have found that PNEO measures such as land use mix entropy [19][20][21], population density [19,21,22], traffic intersection density [13,[23][24][25][26] and proximity to recreation areas [26][27][28] influence the PA levels of older adults. While these types of PNEO measures are reliable in representing the objective physical characteristics of the neighbourhood environment that can strongly influence the PA level in older adults, in some cases, local considerations are also needed.…”
Section: Formulation Of Conceptual Modelmentioning
confidence: 97%
“…The increasing ageing of the population and the ensuing huge social and economic pressure have become a severe test for China's society today and will also in uence China for a long time in the future [1]. It is estimated that the number of elderly people aged > 60 years in China will increase from 15.5% (212 million) in 2014 to 28.0% (402 million) in 2040, and the number of elderly people aged > 80 years will increase from 22.6 million in 2013 to 90.4 million in 2050, allowing China to become the country with the largest number of elderly individuals in the world [2]. Considering the increasing ageing population and the fact that the prevalence of diseases is closely related to age, it is hypothesized that any increase in dysfunction will reduce the physical activity of the elderly.…”
Section: Introductionmentioning
confidence: 99%